Frontend Implementation on EngVenture Application at IntSys Research Lab - Nurhana Rifki, Slamet Ikhvan; Gamayanto, Indra; Wibowo, Sasono; Sirwenda, Alfian Bisma Daniswara; Ismanto, Ivan; Kurniawan, Michael Christ (Politeknik Negeri Batam, 2025)
In today's digital era, the use of mobile applications for English learning is increasingly popular as an alternative to self-study. However, many available applications still lack the ability to provide an interactive, adaptive, and enjoyable learning experience, and do not provide integrated proficiency measurement features such as the TOEFL test. This research focuses on the frontend implementation of the EngVenture application, an English learning platform developed at IntSys Research Lab using the Rapid Application Development (RAD) method. This application is designed to address these issues by integrating gamification elements and a TOEFL-like practice test system to increase engagement and measure user progress. Data were collected through literature studies and questionnaires distributed to 100 respondents from various educational levels. The results showed that 82% of respondents needed a fun learning medium, 92% wanted a TOEFL test feature, and 88% were interested in the gamification feature. The application was developed using Flutter and Dart, with a responsive UI/UX design and real-time feedback features. System testing was conducted using two methods: black-box User Acceptance Testing (UAT) to assess functionality, and a System Usability Scale (SUS) to measure the application's usability. Test results showed that all features functioned well, with an average SUS score of 84.25, which falls into the Acceptable (Grade B+, Excellent) category. These results demonstrate that EngVenture meets user needs in terms of functionality and usability, and has the potential to become an interactive and effective English language learning tool.